Electrospinning of PAN/Ag NPs nanofiber membrane with antibacterial properties. Issue 10 (4th March 2019) - Wang, Chenrong; Wang, Wei; Zhang, Lishan; Zhong, Shan; Yu, Dan
Abstract: Abstract : Durable antibacterial PAN/Ag NPs nanofiber membrane was prepared by electrospinning. In this study, Ag NPs were composed by applying polyvinyl pyrrolidone as a dispersant and sodium borohydride (NaBH4 ) as a reductant. The composite nanofiber films and silver nanoparticles were characterized and tested by transmission electron microscopy, scanning electron microscopy, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, and Brunauer Emmett Teller (BET) and thermogravimetric analysis test. The specific surface area of PAN/Ag NPs (1%) and PAN/Ag NPs (3%) nanofiber membrane were about 25.00 m 2 /g calculated by the BET equation. It can be seen that the pore sizes of PAN, PAN/Ag NPs (1%), and PAN/Ag NPs (3%) nanofiber membranes were mainly distributed between 30 and 40 nm. The maximum removal rate of PM10, PM2.5, and PM1.0 was about 94%, 89%, and 82%, respectively, indicating it has a good filtering effect. The results also demonstrated that this membrane has bacterial reduction of over 99.9% for E. coli and S. aureus, respectively. In addition, the thermal stability of the fiber membrane with Ag NPs has no clear difference when compared to pure PAN nanofiber membrane and also has better moisture conductivity, indicating it is a potential candidate applied in biopharmaceutical antiseptic protection products.